An Entropy Measure of Non-Stationary Processes - Ling Feng Liu; Han Ping Hu; Ya Shuang Deng; Nai Da Ding (Entropy, 2014)
Shannon’s source entropy formula is not appropriate to measure the uncertainty of non-stationary processes. In this paper, we propose a new entropy measure for non-stationary processes, which is greater than or equal to Shannon’s source entropy. The maximum entropy of the non-stationary process has been considered, and it can be used as a design guideline in cryptography.